Model of inquiry strategies for the development of critical and creative thinking in primary school students - Vásquez, Edith (2022)
The objective of this research was to develop a model of inquiry strategies for the development of critical and creative thinking in students of the sixth grade of primary education in Lajas, Chota (Peru). Twenty-three students participated who made up the study population and sample. The research carried out is of a direct and proactive descriptive level, with a mixed methodological approach. The instruments for data collection were developed based on the study variables with the Likert scale and were applied to students, teachers, directors, and parents. Thanks to the information obtained as a diagnosis, the starting point was obtained to elaborate the proposed model. The problem observed was that students and teachers had limitations concerning critical and creative thinking; this allowed the development of the proposed inquiry model, which was validated through expert judgment. Furthermore, it was concluded that the students had a low level of critical and creative thinking development, constituting one more reason to design the model.